Application of Customary Criminal Penalty On Cases Involving Women - Wadjo, Hadibah Zachra; Toule, Elsa Rina Maya; Fadillah, Astuti Nur (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Violence against women is still taking place. Nowadays, issues involving women are increasingly becoming one of the crucial issues in society, not only at the national level, but also at the global level.Purposes of the Research: The purpose of this study is to find out about the application of customary criminal penalties to cases involving women.Methods of the Research: Normative legal research is carried out by examining laws and regulations, jurisprudence and values that lives in society.Results of the Research: The application of penalties for violators in Negeri Amahai, Negeri Haruru, Negeri Nua Nea, Negeri Rutah, and Negeri Souhoku, Negeri Tamilouw highly respects traditional values, which always protect their regions. The customs of their ancestors, until now still exist in people's lives. In fact, until now, the existence of indigenous peoples in several countries in Central Maluku is still maintained, and customary law is maintained by the people of Central Maluku because customary law is pure and can reduce conflicts and erase the stains contained in society.